2001
DOI: 10.1136/pmj.77.911.578
|View full text |Cite
|
Sign up to set email alerts
|

Why do some people look older than they should?

Abstract: Background-As a component of studies on biological age, the age of subjects from their appearance (perceived age) was estimated. Objective-To determine the factors associated with looking older. Methods-Cross sectional study of London civil servants (318 men, 129 women) in the Department of the Environment study. Perceived age was recorded by an observer and the diVerence between this age and chronological age was analysed according to 20 diVerent variables. Results-Men had an average perceived age of 0.37 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
1
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(41 citation statements)
references
References 16 publications
0
39
1
1
Order By: Relevance
“…With age, muscular atrophy or modifications of subcutaneous adipose tissue play an important role in the facial characteristics of men and women, as in the specific distribution of peri-oral wrinkles and sagging chin in elderly women, versus deep expression wrinkles which are more common in aging men. This contributes to the perceived age of men and women, albeit in a non-dramatic fashion, as shown in studies where men have been found to appear 0.37 years older than their age and women 0.54 years younger [71].…”
Section: Muscular Mass and Body Fatmentioning
confidence: 90%
“…With age, muscular atrophy or modifications of subcutaneous adipose tissue play an important role in the facial characteristics of men and women, as in the specific distribution of peri-oral wrinkles and sagging chin in elderly women, versus deep expression wrinkles which are more common in aging men. This contributes to the perceived age of men and women, albeit in a non-dramatic fashion, as shown in studies where men have been found to appear 0.37 years older than their age and women 0.54 years younger [71].…”
Section: Muscular Mass and Body Fatmentioning
confidence: 90%
“…The number of assessors used in perceived age studies has been diverse and two contrasting instances of this are Bulpitt et al (2001) who used three assessors for age judgments and Fink et al (2006) who used 430 assessors. Furthermore, the age, gender and ageing expertise of assessors has been varied; for example, Yamaguchi and Oda (1999) used 'naïve' undergraduate students, Christensen et al (2004) used older female geriatric nurses, Rikkert (1999) used four experienced geriatricians, and Burt and Perrett (1995) used a combination of old, young, male and female naïve assessors.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 This practice assumes that the perceived age of a patient correlates with age-related disease and mortality, and thus that patients appearing older than their chronological age are more likely to be in poor health, compared with patients appearing their actual age. Previous studies have found that male pattern baldness, 3 grey hair, 3,4 and facial wrinkles 4,5 as well as presence of arcus corneae 3 are all associated with looking old for one's age.…”
mentioning
confidence: 99%